ANALYTICAL STUDY OF SELECTED PROMINENT TRAVELOGUES IN URDU LITERATURE - Dr. Shahabuddin; Dr. Muhammad Sulaiman; Dr. Taqwim ul Haq (Journal of Religion and Society, 2024)
Travelogue writing in Urdu literature has evolved into a significant literary genre, combining personal experiences with cultural, historical, and geographical observations. This study examines the stylistic and thematic diversity of selected prominent Urdu travelogues, highlighting their linguistic richness, narrative depth, and socio-cultural insights. Urdu travelogues serve not only as records of personal journeys but also as literary works that capture the essence of different regions, traditions, and civilizations. The research explores the major Urdu travel writers, including Ibn Insha, Mustansar Hussain Tarar, and Raza Ali Abidi, analyzing their distinct writing styles and thematic approaches. It also investigates the evolution of Urdu travelogue writing from early religious and historical accounts to modern, creatively expressive narratives. The study further compares travelogues with other literary genres such as autobiographies, novels, and journalistic travel accounts, emphasizing their unique storytelling techniques. Moreover, this research identifies the strengths and limitations of Urdu travel writing, discussing its contribution to literature, its artistic merits, and areas that require further development. In the contemporary era, digital media and globalization have opened new avenues for Urdu travel literature, making it imperative to adapt this genre to modern storytelling trends. The findings suggest that Urdu travelogues, with their blend of observation, humor, and critical insight, remain an invaluable part of literary heritage, offering readers both knowledge and entertainment. Keywords: Urdu Travelogue, Ibn Insha, Mustansar Hussain Tarar, Urdu Literature, Travel Writing, Narrative Style, Cultural Representation, Historical Perspectives, Humor in Travelogues, Literary Analysis